Determinants of Bank Liquidity in Nepal - Raghu Bir Bista; Priyanka Basnet (Yayasan Ahmar Cendekia Indonesia, 2020)
This paper examines determinants of bank liquidity of the commercial bank in Nepal based on 12 years long time series data base from 2004 to 2015, employing the econometric model. As a result, the bank liquidity of the commercial bank has fluctuation and instable trend line indicating the risk of liquidity crunch. Similarly, deposit, capital adequacy, remittance and bank size are determinants of bank liquidity of the commercial bank out of which deposit is prevalent to increase bank liquidity and capital adequacy is key to decrease it. In long term, capital adequacy, bank size and government expenditure increase bank liquidity of the commercial bank but deposit decreases it. Thus, internal variables influence bank liquidity more than macroeconomic variables. Therefore, the commercial banks should maintain bank liquidity in short period and in long period for achievement of financial health, stability and growth as per mention regulatory provisions and criteria of the monetary policy and the monetary policy should be formulated to maintain short and long term bank liquidity in accordance with IMF standards and guidelines for reducing the potential risk of liquidity crunch as result of the variation of macro-economic variables and of international global trade and oil price and production.